2018
DOI: 10.1371/journal.pone.0207055
|View full text |Cite|
|
Sign up to set email alerts
|

Gender disparities in depression severity and coping among people living with HIV/AIDS in Kolkata, India

Abstract: People living with HIV/AIDS (PLH) experience high rates of depression and related psychosocial risk factors that vary by gender. This study examines gender differences in depression severity among antiretroviral therapy (ART) patients (n = 362) from a large government ART clinic in Kolkata, India. Hypotheses for multiple linear regression models were guided by an integrated gendered stress process model focusing on variables reflecting social status (age, partner status), stressors (stigma), and resources (inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
3
12
1
Order By: Relevance
“…Among the socio-demographic factors, the female gender is the most frequently associated with depression and anxiety [21,23,[27][28][29][30][31]. These findings are consistent with other reviews focused on the general population and healthcare workers during the pandemic [6,7] and more studies before COVID-19 [19,34,35]. Previous research suggests that this gender disparity may be mediated by variables that concern work, economic, educational, neuro-hormonal, psychological and genetic aspects [34,[36][37][38].…”
Section: Discussionsupporting
confidence: 86%
“…Among the socio-demographic factors, the female gender is the most frequently associated with depression and anxiety [21,23,[27][28][29][30][31]. These findings are consistent with other reviews focused on the general population and healthcare workers during the pandemic [6,7] and more studies before COVID-19 [19,34,35]. Previous research suggests that this gender disparity may be mediated by variables that concern work, economic, educational, neuro-hormonal, psychological and genetic aspects [34,[36][37][38].…”
Section: Discussionsupporting
confidence: 86%
“…Unlike many studies where the percentage of females were found to be higher than the males, [9][10][11][12][13] in the present study it is observed that male cases were higher compared to females by 10% and could be due to better awareness and diminished fear of stigma.…”
Section: Discussioncontrasting
confidence: 96%
“…As found in SARSrelated stigma studies, media miscommunications of risk mitigation strategies and inconsistent health policy have augmented uncertainty toward sudden viral epi and pandemics (Lee et al, 2005) resulting in widespread fear and anxiety. Previous scientific studies have shown that the internalized HIV stigma was a strong predictor of depression (Swendeman et al, 2018). The influence of COVID-19 stigma on the mental status of patients is worth discussing in future studies.…”
Section: Discussionmentioning
confidence: 89%